Development of Biodiversity Encyclopedia Based on Flipbook to Improve Student Learning Outcomes in Senior High School 6 Samarinda - Sutiwi; Elsje Theodora Maasawet; Muh Amir Masruhim; Usman Usman; Herliani Herliani; Ahmad Ahmad (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop a flipbook-based encyclopedia on the biodiversity of the Plantae kingdom for Grade X students at SMAN 6 Samarinda to enhance their learning outcomes. The research employed the ADDIE development model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. A total of 30 students participated in the implementation stage. The effectiveness of the product was evaluated using a one-group pretest-posttest design. Data were collected through interviews, needs analysis questionnaires, expert validation sheets, teacher assessments, student response questionnaires, and pretest-posttest multiple-choice questions. The feasibility results from experts comprising material, media, and language specialists showed high validity, with scores of 91.75, 78.88, and 90% respectively, indicating the product is "very feasible" for use. Student response data also supported this, with a practicality score of 89.6%, suggesting students found the encyclopedia engaging and beneficial. Furthermore, the N-gain analysis revealed a high effectiveness category, with an average gain score of 0.81. These results suggest that the developed flipbook-based encyclopedia effectively supports improves student learning outcomes in biology, particularly in the biodiversity topic.